Odpowiedzi

2010-03-24T16:15:38+01:00
2*2+1=9-2*2
4+1=9-4
5=5
Tak
1 5 1
2010-03-24T16:17:53+01:00
A) 2x+1= 9-2x, x=2
2*2+1=9-2*2
4+1=9-4
5=5 spełnia równanie
b) 3(2x-5)= 1- 4x, dla x= 1.5
3(2*1,5-5)=1-4*1,5
9-15=1-6
-6=-5 nie spełnia równanie
c) 4(y-6)-3y=2(y-9), dla y= -6
4(-6-6)-3*(-6)=2(-6-9)
4(-12)+18=2(-15)
-48+18=-30
-30=-30 spełnia równanie
3 5 3
2010-03-24T16:18:16+01:00
A) 2x+1= 9-2x, x=2
2x+2x=9-1
2*2+2*2=8
4+4=8
8=8
TAK

b) 3(2x-5)= 1- 4x, dla x= 1.5
6x-15=1-4x
6x+4x=1+16
6*1,5+4*1,5=17
9+6=17
15=17
NIE

c) 4(y-6)-3y=2(y-9), dla y= -6
4y-24-3y=2y-18
4y-3y-2y=-18+24
-y=-6
-(-6)=-6
6=-6
NIE
1 5 1